The effects of vaginal gel from Myrtus communis on the sexual function of married women during reproductive aging: A study protocol for a randomized controlled trial - Bahareh khajehpour; Raheleh Babazadeh; Roshanak Salari; Jamshid Jamali; Malihe Mahmoudinia (PLoS ONE, 2026)
Introduction Human sexuality is an important aspect of functionality, and many patients believe that it determines their quality of life. Sexual dysfunction can lead to stress, strained relationships, and a decrease in self-esteem. The majority of modern medical treatments for improving female sexual function are associated with significant side effects and high costs. Traditionally, M. communis has been used to treat sexual impotence. Here, we present the protocol of an interventional clinical phase II study to test the hypothesis that vaginal gel containing Myrtus communis extract can improve sexual function in women of reproductive age. Methods/Design In a prospective, randomized, placebo-controlled and highly blind clinical phase II trial, 80 women aged 18--40 years with sexual dysfunction meeting the inclusion criteria will be randomized to an intervention group receiving a vaginal gel containing myrtle leaf extract (n = 38) or an active control group receiving a placebo gel with an identical appearance (n = 38). Randomization will be performed via a permuted block technique with random allocation software. This study will be conducted at the women’s clinic of Imam Reza Hospital in Mashhad. Blinded assessments of outcome variables will be conducted twice: before treatment and one month after treatment. The primary outcome measure was sexual function. Discussion This randomized controlled clinical trial evaluates the efficacy of the vaginal gel Myrtus communis on the sexual function of married women during reproductive age. The study design presented here fulfills the criteria of a high-quality clinical phase II trial of sexual function. Trial registration IRCT.behdasht.gov.ir Identifier: IRCT20230723058892N1